Tenancy Transition and the Effect of Liberalisation on Agricultural Land Leasing. (September 2019) - Rao, Ch. Sankar
This article studies tenancy transition in India during 2002–2012 and critically assesses the proposed Model Agricultural Land Leasing Act, 2016 in addressing the country's current tenancy problems. The article is based on the National Sample Survey Organisation data of the 59th and 70th Rounds. Tenancy in India during the period studied has seen the increasing dominance of large-size farm holdings which have posed challenges to agriculture in India. The legalisation of leases, without disturbing the ownership rights of land owners, is essential for tenants and ensures them security, institutional credit and other governmental benefits. However, a complete liberalisation of the lease market without any legal stipulation on the duration, amount and registration of the lease, and the legal acceptability of lease documents to access institutional credit, crop insurance and other subsidised inputs may not provide a level playing field to the tenant farmer, especially when the lessor is rich and powerful. These concerns need to be addressed by the Model Act 2016 so as not to impinge on the goals of equity and efficiency enshrined in the Act. These concerns should also be addressed by all state governments as they frame tenancy laws in the future.